Strategies for comparative research in political science - Peters, B. Guy, 1944- (Houndmills, Basingstoke, Hampshire, UK Palgrave Macmillan, 2013)
Written by a prominent figure in the field, this book provides an accessible introduction to comparative methodology. Drawing on a wide range of approaches throughout, it is essential reading for anyone wanting to understand or research in this major area of political science.
Keywords: Ciencia política -- Investigación -- Metodología